Utility of an index metacarpal cortical thickness application as an osteoporosis screen in distal radius fracture patients aged over 50. Issue 6 (12th March 2020) - Hymer, Isobel; Sivakumar, Brahman; Bindra, Randipsingh; Awal, Wasim; Robinson, Ann
Abstract: Background: Following wrist fracture, it is desirable to identify patients with osteoporosis. A smartphone‐based application (BoneGauge) that uses second metacarpal cortical thickness ratio (2MCP) measured on X‐ray has been proposed. This study aims to validate this application using dual‐energy X‐ray absorptiometry scan in a cohort of patients with distal radius fractures. Methods: Thirty subjects aged 50 and over who sustained low‐energy fractures of the radius were recruited and measurements were completed by two independent observers using the application. Results: The interrater reliability as a screening tool was insufficient ( κ = 0.61). Using the 2MCP threshold of 60% for detection of osteopaenia or osteoporosis, we found insufficient correlation between the dual‐energy X‐ray absorptiometry scan and the two sets of readings using the application ( κ = 0.28 and 0.35, respectively). Conclusion: On the basis of these results, 2MCP of 60% is not sensitive enough to be used as a screening tool via a smartphone application for assessment of osteoporosis risk. Abstract : A smartphone‐based application (BoneGauge) that uses the second metacarpal cortical thickness ratio (2MCP) measured on X‐ray has been proposed. This study aims to validate this application using dual‐energy X‐ray absorptiometry scan in a cohort of patients with distal radius fractures.